The Long Non-Coding RNA FAM222A-AS1 Negatively Modulates MiR-Let-7f to Promote Colorectal Cancer Progression - Song, Mengmeng; Li, Ye; Chen, Zhewen; Zhang, Jie; Yang, Liuqing; Zhang, Fan; Song, Chunhua; Miao, Mingyong; Chang, Wenjun; Shi, Hanping (Frontiers in Oncology, 2022)
Accumulating evidence indicates that lncRNAs are potential biomarkers and key regulators of tumor development and progression. The present study aimed to screen abnormal expression lncRNAs and investigate the mechanisms underlying the function in the progression of colorectal cancer (CRC). Potential CRC prognosis-associated dysregulated lncRNAs were screened and identified using bioinformatics analysis. Loss/gain-of-function experiments were performed to detect the biological roles of FAM222A-AS1 in CRC cell phenotypes in vitro and in vivo. The potential microRNAs that interact with FAM222A-AS1 were identified using online tools and were verified using qRT-PCR and luciferase reporter assay. The expression of FAM222A-AS1 is significantly upregulated in CRC tumor samples and cell lines. CRC patients with elevated FAM222A-AS1 expression in the tumor samples had unfavorable overall survival and disease-free survival. Silencing FAM222A-AS1 expression significantly inhibited CRC cell proliferation, migration, and invasion both in vitro and in vivo. Furthermore, FAM222A-AS1 was mainly distributed in the cytoplasm. It may directly bound to miR-let-7f and inhibit its expression and upregulate MYH9. In summary, FAM222A-AS1, as a novel oncogene in CRC, may promote the CRC progression by inhibiting miR-let-7f/MYH9 axis. The FAM222A-AS1/miR-let-7f/MYH9 signaling pathway may be a novel valuable target for inhibiting CRC.